Proteomic Analysis of Serum in Cardiac Transthyretin Amyloidosis: Diagnostic and Prognostic Implications for Biomarker Discovery - Joanna Waś; Monika Gawor-Prokopczyk; Agnieszka Sioma; Rafał Szewczyk; Aleksandra Pel; Jolanta Krzysztoń-Russjan; Magdalena Niedolistek; Dorota Sokołowska; Jacek Grzybowski; Łukasz Mazurkiewicz (Biomedicines)
Background/Objectives: Having serum biomarkers available for cardiac transthyretin amyloidosis (ATTR-CA) would be beneficial for diagnosis and prognosis. This study aimed to identify potential ATTR-CA biomarkers through proteomic analysis. Patients and Methods: Serum proteomic analyses were conducted on 15 ATTR-CA patients before receiving treatment, 11 ATTR-CA patients who had received tafamidis treatment for at least six months, and 13 patients with suspected cardiac amyloidosis who were later ruled out. All patients underwent blood tests, standard 12-lead electrocardiography, transthoracic echocardiography, and 99mTc-DPD scintigraphy. Results: Proteomic analysis revealed significant differences in protein levels among the study groups. Key findings revealed increased levels of several proteins, including ceruloplasmin, apolipoprotein E, SERPINA1, and cDNA FLJ54111 (which is highly similar to serum transferrin), in ATTR-CA patients before receiving specific treatment. There was also a reduction in prothrombin, transferrin, CD14, and alpha-2-macroglobulin. In the ATTR-CA group treated with tafamidis, elevated levels of SERPINA1, paraoxonase 1, and complement C2 were observed. Notably, levels of cDNA FLJ54111 and SERPINA3 were reduced in this group. Compared to the control group, patients with ATTR-CA exhibited higher levels of ceruloplasmin, SERPINA3, and VCAM1, as well as lower levels of ApoA-I, ApoA-II, clusterin, and gelsolin. Controls exhibited elevated levels of transthyretin and prothrombin. Conclusions: This study identified candidate serum biomarkers for diagnosing ATTR-CA and monitoring the effectiveness of tafamidis treatment.